2007
DOI: 10.1038/modpathol.3800748
|View full text |Cite
|
Sign up to set email alerts
|

Colonic neuropathological aspects in patients with intractable constipation due to obstructed defecation

Abstract: One of the most frequent subtypes of constipation is represented by obstructed defecation, and it has recently been reported that these patients may have colonic motor abnormalities in addition to alterations of the anorectal area. However, it is unknown whether these patients display abnormalities of the enteric nervous system, as reported in other groups of constipated subjects. For this reason, we evaluated the neuropathologic aspects of the enteric nervous system in a homogeneous group of patients with obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 59 publications
0
23
0
2
Order By: Relevance
“…An intrinsic dysregulation is a stronger possibility. In constipated patients, a diminished density of interstitial cells of Cajal has been implicated, 32 as has a decrease in the overall population of glial cells 33 . Such defects could feasibly account for the striking truncation of propagation of PS and the spatiotemporal disorganization among consecutive PS 9 …”
Section: Discussionmentioning
confidence: 99%
“…An intrinsic dysregulation is a stronger possibility. In constipated patients, a diminished density of interstitial cells of Cajal has been implicated, 32 as has a decrease in the overall population of glial cells 33 . Such defects could feasibly account for the striking truncation of propagation of PS and the spatiotemporal disorganization among consecutive PS 9 …”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples were processed as previously described 28,31,38,39 . After removal, the surgical specimens were immediately fixed in 10% neutral‐buffered formalin for 24 h and transversal sections obtained.…”
Section: Methodsmentioning
confidence: 99%
“…It is, however, worth noting that, notwithstanding numerous studies present in literature on the various pathophysiologic aspects of OD, almost nil is known concerning its neuropathologic aspects, particularly the ENS. Although alterations of the neuroenteric circuitry have been postulated as a pathophysiologic ground for these patients, 29,30 only one study so far showed that a subgroup of patients with OD and severe, intractable symptoms display abnormalities of the ENS, 31 even though the analysis was done in segments proximal to the rectum.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, we have found a significant decrease of EGC, but not ICC, in both the myenteric and submucosal plexuses of patients with severe constipation due to obstructed defecation refractory to treatment. 21 …”
Section: Evidence For Involvement Of Ecg In Abnormal Gastrointestinalmentioning
confidence: 99%